The Role of Sequential Picture Media in Improving Short Story Writing Skills of Fourth-Grade Elementary School Students - Santi Jumawanti; Hendratno; Wahyu Sukartiningsih (LingPoet: Journal of Linguistics and Literary Research, 2026)
This study examines the role of sequential picture media in improving short story writing skills of fourth-grade elementary school students at SD Negeri 028 Penajam through a descriptive qualitative approach. Data were collected through direct observation and in-depth interviews with the class teacher and selected students. Analysis employed Miles & Huberman's interactive model through data reduction, data presentation, and conclusion drawing, with validity ensured through source and method triangulation. Findings indicate that: (1) conventional writing instruction lacked adequate visual support, creating barriers to student creativity; (2) sequential picture media effectively served as an imagination trigger by providing concrete starting points for story development; (3) the media significantly improved writing quality in terms of story structure, descriptive vocabulary, paragraph coherence, and character development; and (4) it strongly enhanced and sustained student learning motivation. The study recommends systematic, contextual, and high-quality development of sequential picture media as an integral component of Indonesian language learning strategies in elementary schools.